The Yiddish policemen's union : a novel - Chabon, Michael (New York : HarperCollins, 2007)
Alaska, rather than Israel, has become the homeland for the Jews following World War II, detectives investigate the death of a heroin-addled chess prodigy.
Keywords: Jews -- Fiction; Murder -- Investigation -- Fiction; Alaska -- Fiction; Mystery fiction; Alternative histories (Fiction).